Fixed Point Theorems for Generalized Set-Valued Weak θ-Contractions in Complete Metric Spaces - Seong-Hoon Cho (Abstract and Applied Analysis)
In this paper, the notion of generalized set-valued weak θ-contractions is introduced and a new fixed point theorem for such contractions is established in the setting metric spaces. The main result is a generalization of fixed point theorems in the literature. An example and an application to generalized differential equation are given to support the validity of the main theorem.